Isolation and antimicrobial assay of bacillus subtilis from fermented toddy of cocus nucifera - M. KRISHNA MOORTHY,; BIJAYA KUMAR NAYAK,; ANIMA NANDA,; HEMALATHA.R.J, (International Journal of Pharma and Bio Sciences, 2017)
Probiotics is defined as live microorganisms which, when administrated in adequate amounts, confers a health benefit to the host. It has received renewed attention recently from product manufacturers, researches and consumers. Probiotic organisms were isolated from Cocus nucifera’s, the common name, toddy. The bacterial isolates screened out from toddy were identified and confirmed as Bacillus subtilis by bio-chemical methods, gram staining and nucleotide sequencing. Characterization and optimization of its probiotic nature was performed by subjecting the organism for tolerance against NaCl, pH and Bile salt. The organism showed good optimization growth at 4% for bile and 5% for NaCl. The organism was checked for its antimicrobial efficiency against human bacterial pathogens and found satisfactory based on its In-vitro study. From the present study, it was confirmed that the probiotic microbes do have the antibacterial properties in addition to their health benefits.